Strategic Management Accounting Information and Performance: Mediating Effect of Knowledge Management - Maelah, Ruhanita; Mohamed, Baha'a Aldeen Hussein; Amir, Amizawati Mohd (The South East Asian Journal of Management, 2022)
Research Aims: The objective of this study is to examine the relationship ‎between Strategic Management Accounting (SMA) information, Knowledge Management (KM), and the performance of ‎Malaysian hospitals. Design/methodology/approach: A survey is employed, and data is collected using self- administered questionnaires. Responses from 95 Malaysian private hospitals were ‎analysed using Partial Least Squares (PLS) 3.0. Research Findings: The findings indicate that SMA ‎information positively affects ‎performance, and KM mediates the ‎relationship between SMA information and interpretation. Theoretical Contribution/Originality: This study utilised the Resource-Based View (RBV) theory to explain SMA information as a resource and KM as a capability that impacts the competitive advantage of organisations. This study ‎contributes to the line of literature on SMA information and ‎KM in the healthcare sector. Managerial Implication in the South East Asian Context: Findings of this study can be used by managers to improve SMA ‎information and KM in their organisations. Research limitation & Implications: Firstly, the data were collected from a single sector, the healthcare sector, in a developing economy and focused on hospitals. It ‎may be inappropriate for the results of this study to be used for other sectors, such as industrial sectors or in other countries. ‎Secondly, the results from path analysis do not explain for sure how ‎these independent variables influence the dependent variables. ‎Although the path analysis can reveal the significant relationships between the independent and dependent variables, it is insufficient to provide subjective information that may need to ‎be addressed using a qualitative method.